Bulk phase passivation perovskite solar cell and method and application thereof

By introducing guanidine thiocyanate as a passivation layer at the perovskite and hole transport layer interface of perovskite solar cells, the problem of insufficient stability and life of perovskite solar cells under the influence of environmental factors is solved, and a significant improvement in battery efficiency and stability is achieved.

CN119767941APending Publication Date: 2025-04-04HUANENG CLEAN ENERGY RES INST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411993152.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Perovskite solar cells are prone to decomposition or deterioration of performance under the influence of environmental factors such as light, humidity, and temperature, resulting in insufficient stability and life of the battery.

Method used

Guanidine thiocyanate is introduced as a passivation layer at the interface of perovskite and hole transport layer to prevent the chemical reaction of perovskites from contacting hole transport layers such as nickel oxide, and improve the crystalline quality and charge transport performance of perovskites.

Benefits of technology

It significantly improves the efficiency of perovskite solar cells, enhances the stability and life of the battery, and reduces the interface recombination rate. It is suitable for various occasions where efficient and stable solar power is required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119767941A_ABST
    Figure CN119767941A_ABST
Patent Text Reader

Abstract

The invention provides a bulk phase passivation perovskite solar cell and a method and application thereof, a passivation layer is arranged between a hole transport layer and a perovskite light absorption layer of the solar cell, and the passivation layer is prepared from guanidine thiocyanate. According to the perovskite solar cell, guanidine thiocyanate is introduced into the perovskite and hole transport layer interface to passivate the perovskite buried interface, so that the efficiency of the perovskite solar cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular to a bulk passivated perovskite solar cell and a method and application thereof. Background Art

[0002] Perovskite is the name of a mineral discovered in Russia in 1839. It is named after its unique chemical composition CaTiO3 and the Russian geologist Lev Perovsky. It not only represents a mineral, but also a general term for a class of compounds with a special structure - ABX3 type. With its unique crystal structure and diverse physical and chemical properties, perovskite has gradually become a research hotspot in many disciplines such as physics, chemistry and materials science.

[0003] In recent years, the application of perovskite materials in the field of solar cells has been particularly eye-catching. Since scientists first used perovskite materials (such as CH3NH3PbI3, CH3NH3PbBr3) as sensitizers in dye-sensitized solar cells in 2009 and achieved a photoelectric conversion efficiency of about 4%, perovskite solar cells have quickly become the research frontier in the photovoltaic field with their high conversion efficiency, low-cost preparation, and easy adjustment of band gap. This breakthrough not only laid a solid foundation for the development of perovskite solar cells, but also paved the way for the future development of high-efficiency perovskite photovoltaic technology.

[0004] Over the past decade, the efficiency of perovskite solar cells has increased at an astonishing rate. From the initial 4% to the current photoelectric conversion efficiency of small-area single-junction perovskite solar cells prepared in the laboratory, which has exceeded 26.7%, this rate of progress has even surpassed the 60-year development of crystalline silicon cells. The reason why perovskite solar cells have been able to make such remarkable progress in a short period of time is mainly due to their unique crystal structure and material properties. The characteristics of perovskite materials such as adjustable band gap, high carrier mobility, and long exciton diffusion length enable perovskite solar cells to more effectively capture photons and convert them into electrical energy under lighting conditions. In addition, the preparation process of perovskite materials is relatively simple and low-cost, which also provides the possibility for the industrial application of perovskite solar cells.

[0005] Although perovskite solar cells have shown great potential in terms of efficiency and cost, they still face some challenges and problems in practical applications. First, the stability of perovskite materials is a major problem in current research. Because perovskite materials are prone to decomposition or performance degradation under the influence of environmental factors such as light, humidity, and temperature, the stability and life of the battery are insufficient. Therefore, how to improve the stability of perovskite materials and extend the service life of the battery is one of the important directions of current perovskite solar cell research. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a bulk passivated perovskite solar cell and a method and application thereof, which passivates the buried perovskite interface by introducing guanidine thiocyanate at the interface between the perovskite and the hole transport layer, thereby improving the efficiency of the perovskite solar cell.

[0007] To achieve the above object, the present invention provides the following technical solution: a bulk passivated perovskite solar cell, wherein a passivation layer is arranged between the hole transport layer and the perovskite light absorbing layer of the solar cell, and the passivation layer is prepared by guanidine thiocyanate.

[0008] Furthermore, the passivation layer is prepared using a guanidine thiocyanate solution with a concentration of 1 mg / mL and a thickness of 2 nm to 10 nm.

[0009] Furthermore, the hole transport layer is made of NiO x ,CuSCN,CuO x Or one of CuI, with a thickness of 20nm~40nm.

[0010] Furthermore, the perovskite light absorbing layer adopts (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor was prepared with a thickness of 300nm~700nm.

[0011] Furthermore, the solar cell includes, from bottom to top, a substrate, a hole transport layer, a passivation layer, a perovskite light absorption layer, an electron transport layer and a top electrode.

[0012] Furthermore, the substrate is a transparent conductive glass substrate with a thickness of 200-400 nm; the electron transport layer is prepared from TiO2, SnO2 or fullerene and a fullerene derivative with a thickness of 10 nm-100 nm; the top electrode is prepared from one of gold, silver, copper, graphite or amorphous carbon with a thickness of 50-500 nm.

[0013] The present invention also provides a method for preparing a bulk passivated perovskite solar cell, the specific steps of which are as follows: A hole transport layer solution is prepared on a substrate by magnetron sputtering and annealed at a temperature of 200° C. to 400° C. to obtain a hole transport layer; Spin-coat the passivation layer solution on the hole transport layer at a speed of 3000 rpm to 6000 rpm for 30 seconds, and anneal at 80° C. to 120° C. for 10 minutes to obtain a passivation layer; The perovskite precursor solution was spin-coated on the passivation layer at a speed of 1500 rpm to 2000 rpm for 10 s, and at a speed of 5000 rpm for 40 s to 50 s. 200 μL of chlorobenzene was added as an anti-solvent 10 s before the end of the spin coating. The perovskite film was then annealed on a hot stage at 100 °C for 25 to 30 minutes to obtain a perovskite light-absorbing layer. The electron transport layer is prepared on the perovskite light absorbing layer by vacuum evaporation method; A top electrode is prepared on the electron transport layer by vacuum evaporation to obtain a solar cell.

[0014] Furthermore, in the step of preparing an electron transport layer on the perovskite light absorbing layer by vacuum evaporation, specifically: the evaporation rate is 0.3 Å / s ~0.5 Å / s.

[0015] Furthermore, in the step of preparing the top electrode on the electron transport layer by vacuum evaporation, specifically: the evaporation rate is 0.3 Å / s ~0.6 Å / s.

[0016] The present invention also provides a bulk passivated perovskite solar cell system, wherein the system is provided with the above solar cell.

[0017] Compared with the prior art, the present invention has at least the following beneficial effects: The present invention provides a bulk passivated perovskite solar cell. By introducing guanidine thiocyanate as a passivation layer between the perovskite and the hole transport layer, the present invention effectively avoids the chemical reaction that may be caused by direct contact between the perovskite and the hole transport layer such as nickel oxide. Such chemical reaction usually leads to a decrease in the performance of the perovskite cell. The introduction of guanidine thiocyanate not only prevents these adverse reactions, but also reduces the risk of the cell being damaged by the thiocyanate radical (SCN - ) and the lead ions (Pb 2+ ) for coordination, significantly improving the crystal quality and charge transport performance of perovskite. Together, these improvements have significantly improved the efficiency of perovskite solar cells.

[0018] Furthermore, guanidine thiocyanate as a passivation layer material can effectively reduce the interface defects between the perovskite light absorption layer and the hole transport layer, thereby reducing the interface recombination rate and improving the stability and life of the battery. This is of great significance for the long-term stable operation of perovskite solar cells in practical applications.

[0019] Furthermore, the present invention optimizes the battery structure by precisely controlling the thickness of the passivation layer (2nm~10nm) and the thickness of the hole transport layer and the perovskite light absorption layer. This optimization not only improves the photoelectric conversion efficiency of the battery, but also enables the battery to have better stability and reliability while maintaining high efficiency.

[0020] Furthermore, since the bulk passivated perovskite solar cell provided by the present invention has high efficiency, high stability and optimized structural characteristics, it can be widely used in various occasions requiring efficient and stable solar power sources, such as rooftop photovoltaics, curtain wall photovoltaics, portable devices, aerospace, and electric vehicles.

[0021] Furthermore, the implementation of the present invention not only provides new ideas and methods for the research of perovskite solar cells, but also lays a solid foundation for promoting the further development of perovskite solar cell technology. With the continuous advancement of technology and the reduction of costs, perovskite solar cells are expected to become an important force in the field of clean energy in the future.

[0022] In summary, a bulk passivated perovskite solar cell has achieved significant improvements in cell efficiency, stability and structural optimization by introducing guanidine thiocyanate as a passivation layer material, providing strong support for the practical application of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of the structure of a bulk passivated perovskite solar cell; Figure 2 JV curves of batteries of embodiment (solid line) and comparative example (dashed line).

[0024] In the attached figure: 1, substrate; 2, hole transport layer; 3, passivation layer; 4, perovskite light absorption layer; 5, electron transport layer; 6, top electrode. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0026] like Figure 1 As shown, the present invention provides a bulk passivated perovskite solar cell, which includes, from bottom to top, a substrate 1, a hole transport layer 2, a passivation layer 3, a perovskite light absorption layer 4, an electron transport layer 5 and a top electrode 6. The passivation layer of the present invention is prepared by guanidine thiocyanate (GuSCN), and the thickness of the passivation layer is 2nm~10nm, preferably 2nm~5nm, and most preferably 3nm. The present invention passivates the buried interface of the perovskite by introducing guanidine thiocyanate at the interface between the perovskite and the hole transport layer. The perovskite directly contacts the nickel oxide hole transport layer and a chemical reaction occurs, resulting in a decrease in the performance of the perovskite cell. The introduction of guanidine thiocyanate can avoid the occurrence of this reaction. At the same time, the thiocyanate (SCN in guanidine thiocyanate) - ) can react with the lead ions (Pb 2+ ) coordination, improving the crystal quality and charge transfer performance of perovskite, thereby improving the efficiency of perovskite solar cells.

[0027] When preparing the above-mentioned perovskite-based solar cell, the specific steps are as follows: Step 1: Clean the base with acetone, isopropyl alcohol, and deionized water in turn, blow dry and set aside.

[0028] Step 2: preparing a hole transport layer solution on a substrate by magnetron sputtering and annealing at a temperature of 200° C. to 400° C. to obtain a hole transport layer; Step 3: Spin-coat the passivation layer solution on the hole transport layer at a rotation speed of 3000 rpm to 6000 rpm for 30 seconds, and anneal at 80° C. to 120° C. for 10 minutes to obtain a passivation layer.

[0029] Step 4: Apply the perovskite precursor solution on the passivation layer, spin coating at a speed of 1500rpm~2000rpm for 10s, spin coating at a speed of 5000rpm for 40s~50s, quickly add 200μL of chlorobenzene as an anti-solvent 10s before the end of spin coating, and then anneal the perovskite film at 100℃ on a hot stage for 25~30 minutes to obtain a perovskite light-absorbing layer.

[0030] Step 5: Prepare the electron transport layer C on the perovskite light absorbing layer by vacuum evaporation 60 , evaporation rate 0.3Å / s~0.5Å / s.

[0031] Step 6. Finally, a top electrode is prepared on the electron transport layer by vacuum evaporation at a rate of 0.3Å / s~0.6Å / s to obtain a solar cell.

[0032] Preferably, the substrate of the present invention is a transparent conductive glass substrate, the transparent conductive glass is indium tin oxide (FTO), and the thickness of the substrate is 200nm~400nm, preferably 250nm~350nm; specifically 290nm, 300nm, 310nm, 320nm, etc.; Preferably, the hole transport layer solution is NiO x ,CuSCN,CuO x or CuI solution, more preferably NiO x (x is 1 to 1.5), the thickness is 20 nm to 40 nm, preferably 25 nm to 35 nm, and more preferably 30 nm.

[0033] Preferably, the passivation layer solution is a guanidine thiocyanate solution with a concentration of 1 mg / mL, and the solvent is DMSO.

[0034] Preferably, the perovskite precursor solution is (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05)3 perovskite precursor solution, the concentration is 1.5 mol / L, the solvent is DMF:DMSO=4:1; the thickness of the perovskite light absorbing layer is 300nm~700nm, preferably 300nm~500nm, and more preferably 400nm~500nm.

[0035] Preferably, the electron transport layer is prepared using TiO2, SnO2 or one of fullerene and fullerene derivatives, more preferably C 60 The thickness of the electron transport layer is 10 nm to 100 nm, preferably 20 nm to 80 nm, more preferably 30 nm to 60 nm, and most preferably 40 nm to 50 nm.

[0036] Preferably, the top electrode is made of one of gold, silver, copper, graphite or amorphous carbon, more preferably gold; the thickness of the top electrode is 50nm~500nm, preferably 100nm~400nm, more preferably 100nm~200nm.

[0037] Example 1 The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0038] Preparation of NiO on FTO glass substrate by magnetron sputtering x (x is 1-1.5) hole transport layer and annealing, thickness 20nm, annealing temperature 200°C. On the hole transport layer, guanidine thiocyanate solution (concentration 1mg / mL, solvent is DMSO) was spin coated at 5000rpm for 30s, and annealed at 100°C for 10 minutes to form a passivation layer.

[0039] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution (concentration is 1.5mol / L, solvent is DMF:DMSO=4:1), take 100μL of precursor solution and apply it on the passivation layer, spin coating at 2000rpm for 10s, spin coating at 5000rpm for 40s, quickly add 200μL of chlorobenzene as anti-solvent 10s before the end of spin coating, and then anneal the perovskite film at 100℃ on a hot stage for 30 minutes to form a perovskite light-absorbing layer with a thickness of about 400nm.

[0040] The electron transport layer C is prepared on the passivation layer by vacuum evaporation on the perovskite light absorbing layer. 60 , thickness is about 40nm.

[0041] Finally, the top electrode gold is prepared by vacuum evaporation method with a thickness of about 100nm to obtain a solar cell.

[0042] Example 2 The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0043] A CuSCN hole transport layer was prepared on a FTO glass substrate by magnetron sputtering and annealed, with a thickness of 25 nm and an annealing temperature of 300° C. A guanidine thiocyanate solution (concentration 1 mg / mL, solvent DMSO) was spin-coated on the hole transport layer at 3000 rpm for 30 s and annealed at 80° C. for 10 minutes to form a passivation layer.

[0044] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution (concentration is 1.5mol / L, solvent is DMF:DMSO=4:1), take 100μL of precursor solution and apply it on the passivation layer, spin coating at 1500rpm for 10s, spin coating at 5000rpm for 40s, quickly add 200μL of chlorobenzene as anti-solvent 10s before the end of spin coating, and then anneal the perovskite film at 100℃ on a hot stage for 30 minutes to form a perovskite light-absorbing layer with a thickness of about 400nm.

[0045] The electron transport layer TiO2 is prepared on the passivation layer by vacuum evaporation on the perovskite light absorbing layer, and the thickness is about 40nm.

[0046] Finally, the top electrode silver is prepared by vacuum evaporation method with a thickness of about 100nm to obtain a solar cell.

[0047] Example 3 The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0048] CuO prepared by magnetron sputtering on FTO glass substrate x The hole transport layer was annealed to a thickness of 30 nm and an annealing temperature of 400° C. A guanidine thiocyanate solution (concentration 1 mg / mL, solvent DMSO) was spin-coated on the hole transport layer at a speed of 5000 rpm for 30 s and annealed for 10 minutes to form a passivation layer.

[0049] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05)3 Perovskite precursor solution (concentration is 1.5 mol / L, solvent is DMF:DMSO=4:1), take 100μL of precursor solution and apply it on the passivation layer, spin coating at 1800rpm for 10s, spin coating at 5000rpm for 40s, quickly add 200μL of chlorobenzene as anti-solvent 10s before the end of spin coating, and then anneal the perovskite film at 100℃ on a hot stage for 30 minutes to form a perovskite light-absorbing layer with a thickness of about 400nm.

[0050] An electron transport layer SnO2 is prepared on the passivation layer by vacuum evaporation on the perovskite light absorbing layer, with a thickness of about 40 nm.

[0051] Finally, the top electrode copper is prepared by vacuum evaporation method with a thickness of about 100nm to obtain a solar cell. Example 4 The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0052] A CuI hole transport layer was prepared on a FTO glass substrate by magnetron sputtering and annealed, with a thickness of 35 nm and an annealing temperature of 200° C. A guanidine thiocyanate solution (concentration 1 mg / mL, solvent DMSO) was spin-coated on the hole transport layer at a speed of 5000 rpm for 30 s and annealed for 10 minutes to form a passivation layer.

[0053] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution (concentration is 1.5mol / L, solvent is DMF:DMSO=4:1), take 100μL of precursor solution and apply it on the passivation layer, spin coating at 2000rpm for 10s, spin coating at 5000rpm for 40s, quickly add 200μL of chlorobenzene as anti-solvent 10s before the end of spin coating, and then anneal the perovskite film at 100℃ on a hot stage for 30 minutes to form a perovskite light-absorbing layer with a thickness of about 400nm.

[0054] An electron transport layer C50S is prepared on the passivation layer by vacuum evaporation on the perovskite light-absorbing layer, with a thickness of about 40 nm.

[0055] Finally, the top electrode gold is prepared by vacuum evaporation method with a thickness of about 100nm to obtain a solar cell.

[0056] Example 5 The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0057] Preparation of NiO on FTO glass substrate by magnetron sputtering x (x is 1-1.5) hole transport layer and annealing, thickness 40nm, annealing temperature 200°C. On the hole transport layer, guanidine thiocyanate solution (concentration 1mg / mL, solvent is DMSO) was spin coated at 5000rpm for 30s and annealed for 10 minutes to form a passivation layer.

[0058] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution (concentration is 1.5mol / L, solvent is DMF:DMSO=4:1), take 100μL of precursor solution and apply it on the passivation layer, spin coating at 2000rpm for 10s, spin coating at 5000rpm for 40s, quickly add 200μL of chlorobenzene as anti-solvent 10s before the end of spin coating, and then anneal the perovskite film at 100℃ on a hot stage for 30 minutes to form a perovskite light-absorbing layer with a thickness of about 400nm.

[0059] The electron transport layer C is prepared on the passivation layer by vacuum evaporation on the perovskite light absorbing layer. 60 , thickness is about 40nm.

[0060] Finally, the top electrode graphite is prepared by vacuum evaporation method with a thickness of about 100nm to obtain a solar cell.

[0061] Example 6 The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0062] Preparation of NiO on FTO glass substrate by magnetron sputtering x (x is 1-1.5) hole transport layer and annealing, thickness 20nm, annealing temperature 200°C. On the hole transport layer, guanidine thiocyanate solution (concentration 1mg / mL, solvent is DMSO) was spin coated at 5000rpm for 30s and annealed for 10 minutes to form a passivation layer.

[0063] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05)3 Perovskite precursor solution (concentration is 1.5mol / L, solvent is DMF:DMSO=4:1), take 100μL of precursor solution and apply it on the passivation layer, spin coating at 2000rpm for 10s, spin coating at 5000rpm for 40s, quickly add 200μL of chlorobenzene as anti-solvent 10s before the end of spin coating, and then anneal the perovskite film at 100℃ on a hot stage for 30 minutes to form a perovskite light-absorbing layer with a thickness of about 400nm.

[0064] The electron transport layer C is prepared on the passivation layer by vacuum evaporation on the perovskite light absorbing layer. 60 , thickness is about 40nm.

[0065] Finally, amorphous carbon is prepared as the top electrode by vacuum evaporation method with a thickness of about 100 nm to obtain a solar cell.

[0066] Comparative Example 1: The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0067] Preparation of NiO on FTO glass substrate by magnetron sputtering x (x is 1~1.5) hole transport layer and annealing, thickness 20nm, annealing temperature 200℃. Prepared according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution (concentration of 1.5mol / L, solvent DMF:DMSO=4:1), take 100μL of the precursor solution and apply it on the hole transport layer, spin coating at 2000rpm for 10s, spin coating at 5000rpm for 40s, quickly add 200μL of chlorobenzene as anti-solvent 15s before the end of spin coating, and then anneal the perovskite film at 100℃ on a hot stage for 30 minutes to form a perovskite light absorption layer with a thickness of about 400nm. Prepare the electron transport layer C on the passivation layer by vacuum evaporation on the perovskite light absorption layer 60 , with a thickness of about 40nm. Finally, the top electrode gold is prepared by vacuum evaporation method, with a thickness of about 100nm; and a solar cell is obtained.

[0068] The performance of the solar cells prepared in Example 1 and Comparative Example 1 was tested. Under room temperature, a 3A solar simulator was used to test the performance of the solar cells at 100 mW / cm 2 The conversion efficiency of the top and bottom cells prepared in the embodiment was tested under light intensity, and the effective area of ​​the cell was 0.084 cm 2 .

[0069] The test results of the battery prepared in the embodiment are as follows:

[0070] The performance test results of the bottom battery prepared in the comparative example are as follows:

[0071] like Figure 2 As shown, from the battery test results, it can be seen that the battery performance prepared in Example 1 is significantly improved compared with the control example, which indicates that the introduction of guanidine thiocyanate at the interface between the hole transport layer and the perovskite light absorption layer helps to improve the crystallization quality of the perovskite film and the charge transport performance.

Claims

1. A bulk passivated perovskite solar cell, characterized in that: A passivation layer is arranged between the hole transport layer and the perovskite light absorption layer of the solar cell, and the passivation layer is prepared by using guanidine thiocyanate.

2. A bulk passivated perovskite solar cell according to claim 1, characterized in that: The passivation layer was prepared using a guanidine thiocyanate solution with a concentration of 1 mg / mL and a thickness of 2 nm to 10 nm.

3. The bulk passivated perovskite solar cell according to claim 1, characterized in that: The hole transport layer uses NiO x ,CuSCN,CuO x Or one of CuI, with a thickness of 20nm~40nm.

4. The bulk passivated perovskite solar cell according to claim 1, characterized in that: Perovskite light absorbing layer adopts (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor was prepared with a thickness of 300nm~700nm.

5. A bulk passivated perovskite solar cell according to any one of claims 1 to 4, characterized in that: The solar cell comprises, from bottom to top, a substrate (1), a hole transport layer (2), a passivation layer (3), a perovskite light absorption layer (4), an electron transport layer (5) and a top electrode (6).

6. A bulk passivated perovskite solar cell according to claim 5, characterized in that: The substrate (1) is a transparent conductive glass substrate, and the thickness of the substrate is 200nm-400nm; the electron transport layer (5) is prepared by using TiO2, SnO2 or one of fullerene and fullerene derivatives, and the thickness is 10nm-100nm; the top electrode (6) is prepared by using one of gold, silver, copper, graphite or amorphous carbon, and the thickness is 50nm-500nm.

7. The method for preparing a bulk passivated perovskite solar cell according to claim 6, characterized in that: The specific steps are as follows: The hole transport layer solution is prepared on the substrate (1) by magnetron sputtering and annealed at a temperature of 200° C. to 400° C. to obtain a hole transport layer (2); Spin coating the passivation layer solution on the hole transport layer (2) at a rotation speed of 3000 rpm to 6000 rpm for 30 seconds, and annealing at 80° C. to 120° C. for 10 minutes to obtain a passivation layer (3); Spin coating the perovskite precursor solution on the passivation layer (3) at a rotation speed of 1500 rpm to 2000 rpm for 10 seconds, and at a rotation speed of 5000 rpm for 40 seconds to 50 seconds, and then drop 200 μL of chlorobenzene as an anti-solvent 10 seconds before the end of the spin coating, and then anneal the perovskite film at 100° C. on a hot stage for 25 to 30 minutes to obtain a perovskite light absorbing layer (4); Preparing an electron transport layer (5) on the perovskite light absorbing layer (4) by vacuum evaporation; A top electrode (6) is prepared on the electron transport layer (5) by using a vacuum evaporation method to obtain a solar cell.

8. The method for preparing a bulk passivated perovskite solar cell according to claim 7, characterized in that: In the step of preparing the electron transport layer (5) on the perovskite light absorption layer (4) by using a vacuum evaporation method, specifically: the evaporation rate is 0.3Å / s~0.5Å / s.

9. The method for preparing a bulk passivated perovskite solar cell according to claim 7, characterized in that: In the step of preparing the top electrode (6) on the electron transport layer (5) by vacuum evaporation, specifically: the evaporation rate is 0.3Å / s~0.6Å / s.

10. A bulk passivated perovskite solar cell system, characterized in that: The system is provided with the perovskite-based solar cell according to claim 1 or the solar cell prepared by the preparation method according to any one of claims 7 to 9.

Citation Information

Cited By

  • Preparation method of perovskite solar cell

    CN121174889A